2014
DOI: 10.1071/cp13442
|View full text |Cite
|
Sign up to set email alerts
|

Pasture cropping with C4 grasses in a barley–lupin rotation can increase production

Abstract: In southern Australia, intercropping, pasture cropping and overcropping have evolved as techniques to address environmental problems such as dryland salinity and wind erosion and to utilise soil water outside the conventional winter-dominant growing season. We paired three winter-dormant pastures, including two subtropical C4 perennial species (Rhodes grass, Chloris gayana; Gatton panic, Megathyrsus maximus) and the summer-active perennial C3 legume siratro (Macroptilium atropurpureum), with a conventional bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…Lawes et al (2014) reported that pasture cropping with C 4 grasses that are active in summer could be feasible in the Mediterranean environment in Western Australia, provided by agronomic manipulations through row spacing and N treatment. To reduce crop yield losses in such pasturecropping systems, it is important that the pastures remain dormant during the winter months and that soilborne pathogens are not a bottleneck for the cereal crop.…”
Section: Relationship Between Non-symbiotic N 2 Fixation and Soil Promentioning
confidence: 99%
“…Lawes et al (2014) reported that pasture cropping with C 4 grasses that are active in summer could be feasible in the Mediterranean environment in Western Australia, provided by agronomic manipulations through row spacing and N treatment. To reduce crop yield losses in such pasturecropping systems, it is important that the pastures remain dormant during the winter months and that soilborne pathogens are not a bottleneck for the cereal crop.…”
Section: Relationship Between Non-symbiotic N 2 Fixation and Soil Promentioning
confidence: 99%
“…Pasture cropping is a no-tillage technique consisting of sowing annual crops into living perennial pastures during their dormant stage [1,2]. This cropping system combines species with complementary growth periods to diversify the farming systems and improve overall land productivity.…”
Section: Introductionmentioning
confidence: 99%
“…This cropping system combines species with complementary growth periods to diversify the farming systems and improve overall land productivity. Potential environmental benefits of this system are varied, and include increasing soil cover, reducing erosive processes, improving soil structure and organic matter, increasing infiltration and water retention, reducing N lixiviation and sequestering CO 2 [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the wheatbelt region of Western Australia, kikuyu grass (Pennisetum clandestinum) has become well established in the cooler south coast region, and Rhodes (Chloris gayana)-panic (Panicum spp.) grass mixtures are common in the north ( Moore et al 2006;Lawes et al 2014). Tenosols are stabilised by the establishment of kikuyu pastures that produce deeprooting systems (McDowall et al 2003;Nie et al 2008) and these protect and even increase soil carbon (Roper et al 2013b).…”
Section: Avoidance: Adaptation and Alternative Land Usementioning
confidence: 99%